Polyester film and its uses

The use of a specially formulated polyester film with tailored refractive indices and elastic moduli addresses the issues of image distortion and cracking in folding displays, ensuring durability and image quality while maintaining mass production feasibility.

JP7666681B2Active Publication Date: 2025-04-22TOYOBO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024038661
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-28
Filing Date
2024-03-13
Publication Date
2025-04-22
Estimated Expiration
2040-05-14

AI Technical Summary

Technical Problem

Conventional folding displays face challenges with image distortion and cracking in the folding portion due to repeated folding, which affects the durability and visibility of the display.

Method used

A polyester film with specific refractive index ranges in different directions (1.590-1.620 in the bending direction, 1.670-1.700 in the folding direction, and 1.520 or less in the thickness direction) and a density of 1.380g/cm³ is used as the base material for the touch panel module substrate, combined with an elastic modulus of 2.7GPa or less in the bending direction and 4.5GPa or more in the folding direction, to enhance flexibility and resistance to deformation.

Benefits of technology

The solution maintains mass production feasibility while preventing cracks and deformation in the folding portion, ensuring image quality and durability of the folding display, and providing excellent portability and functionality for portable terminal devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666681000003
    Figure 0007666681000003
  • Figure 0007666681000004
    Figure 0007666681000004
  • Figure 0007666681000001
    Figure 0007666681000001
Patent Text Reader

Abstract

To provide a polyester film for a touch panel module substrate of a foldable display which is excellent in mass productivity and causes no cracking at a folded part in order to provide a foldable display with no risk of distortion of an image displayed at the folded part after repeated folding.SOLUTION: There is provided a polyester film for a touch panel module substrate of a foldable display which satisfies the following conditions. (1) The refractive index in the bending direction is 1.590 to 1.620. (2) The refractive index in the direction of a folded part is 1.670 to 1.700. (3) The refractive index in the direction of thickness is 1.520 or less. (4) The density is 1.380 g / cm3 or more (here, the bending direction refers to the direction perpendicular to the folded part when the polyester film is folded.)SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyester film for use as a substrate for a touch panel module of a foldable display, a hard coat film for use as a substrate for a touch panel module of a foldable display, a foldable display, and a mobile terminal device, and relates to a foldable display and a mobile terminal device that are unlikely to suffer from image distortion due to film deformation even when repeatedly folded, and to a polyester film and hard coat film for use as a substrate for a touch panel module of the foldable display. [Background technology]

[0002] As mobile terminal devices become thinner and lighter, smartphones and other mobile terminal devices are becoming more and more popular. While mobile terminal devices are required to have a variety of functions, they are also required to be convenient. For this reason, the mobile terminal devices that are currently in use must be able to perform simple operations with one hand, and must have a small screen size of around 6 inches, since they are assumed to be stored in a pocket or similar.

[0003] On the other hand, tablet devices with screen sizes of 7 to 10 inches are highly functional and can be used not only for video content and music, but also for business purposes, drawing, reading, etc. However, they cannot be operated with one hand, are less portable, and have issues with convenience.

[0004] To achieve these goals, a method has been proposed of connecting multiple displays together to make them more compact (see Patent Document 1), but this method has not become widespread because it leaves a bezel, which means the image is cut off and visibility is reduced.

[0005] In recent years, mobile terminals incorporating flexible displays and foldable displays have been proposed, which provide a large-screen display without interruption of the image and are convenient to carry around.

[0006] Here, in the case of conventional displays and mobile terminal devices that do not have a folding structure, the surface of the display can be protected by a non-flexible material such as glass, but in the case of a folding display, when a one-sided display is formed through a folding part, it is necessary to use a hard coat film that is flexible and can protect the surface. However, in a folding display, the part corresponding to a certain folding part is repeatedly folded, so that the film in that part deforms over time, causing problems such as distorting the image displayed on the display. In addition to the surface protection film, films are used in various parts of the folding display, such as polarizing plates, retardation plates, touch panel substrates, substrates of display cells such as organic EL, and protective members on the back surface, and durability against repeated folding is also required for these films.

[0007] In view of this, a method has been proposed in which the film thickness is partially changed (see Patent Document 2), but this method has the problem of being poorly suited for mass production.

[0008] A method of adjusting the refractive index in the bending direction of a polyester film has also been proposed (see Patent Document 3), but as the refractive index in the bending direction is reduced, the pencil hardness when a hard coat is applied decreases, resulting in a problem of reduced surface protection function for displays. In addition, lowering the refractive index in one direction improves deformation when folded, but increases uniaxial orientation in the folding direction, resulting in problems such as cracks or breakage at the folded portion. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] JP 2010-228391 A [Patent Document 2] JP 2016-155124 A [Patent Document 3] International Publication No. 2018 / 150940 Summary of the Invention [Problem to be solved by the invention]

[0010] The present invention seeks to solve the problems associated with conventional display components as described above, and aims to provide a foldable display that is easy to mass-produce and has no risk of distortion of the image displayed at the folded portion after repeated folding, and a mobile terminal device equipped with such a foldable display, by providing a polyester film for use as a touch panel module substrate for a foldable display that does not produce fold marks or cracks at the folded portion. [Means for solving the problem]

[0011] That is, the present invention comprises the following: 1. A polyester film for use as a substrate for touch panel modules in foldable displays that satisfies the following conditions: (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) Refractive index in the thickness direction is 1.520 or less (4) Density is 1.380 g / cm 3 End (Here, the bending direction refers to the direction perpendicular to the fold when folding the polyester film.) 2. The polyester film for use as a base material for a touch panel module of a folding display as described above in 1, having an elastic modulus of 2.7 GPa or less in the bending direction and an elastic modulus of 4.5 GPa or more in the direction of the folding portion. 3. A polyester film for use as a base material for a touch panel module of a folding display as described in 1 or 2 above, having a total light transmittance of 85% or more, a haze of 3% or less, and a maximum thermal shrinkage of 2% or less. 4. A polyester film for use as a base material for a touch panel module of a foldable display according to any one of claims 1 to 3, which shows no cracks or deformations in a bending resistance evaluation (bending radius of 1.5 mm) after heat treatment at 150°C for 30 minutes. 5. The polyester film for use as a substrate for a touch panel module of a foldable display according to any one of the above items 1 to 4, which has an easy-adhesion layer on at least one surface of the polyester film for use as a substrate for a touch panel module of a foldable display. 6. The polyester film for use as a substrate for a touch panel module of a foldable display according to any one of the above items 1 to 5, which has a hard coat layer having a thickness of 1 to 50 μm on at least one surface of the polyester film for use as a substrate for a touch panel module of a foldable display. 7. A foldable display comprising the polyester film for use as a touch panel module substrate of a foldable display according to any one of claims 1 to 6 above as a substrate film for a touch panel module, the foldable display comprising a substrate film for a single touch panel module that is continuous via a folding portion of the foldable display. 8. A mobile terminal device having the foldable display described in claim 7. Effect of the Invention

[0012] A foldable display using the polyester film for touch panel module substrate of the foldable display of the present invention maintains mass productivity, and the polyester film does not crack at the folding portion, does not deform after repeated folding, and does not cause image distortion at the folding portion of the display. A mobile terminal device equipped with a foldable display using such a polyester film as a touch panel module substrate provides beautiful images, is highly functional, and is convenient in terms of portability, etc. [Brief description of the drawings]

[0013] [Figure 1] FIG. 2 is a schematic diagram showing the bending radius when the foldable display of the present invention is folded. [Diagram 2] FIG. 2 is a schematic diagram showing the bending direction of a polyester film for use as a touch panel module substrate in a foldable display according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] (display) The display in the present invention generally refers to a display device, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc., but LCD, organic EL, and inorganic EL having a bendable structure are preferred. In particular, organic EL and inorganic EL, which can reduce the layer structure, are more preferred, and organic EL, which has a wide color gamut, is even more preferred.

[0015] (Foldable display) A folding display is a single continuous display that can be folded in half or the like when carried. By folding, the size can be halved, improving portability. The bending radius of a folding display is preferably 5 mm or less, and more preferably 3 mm or less. If the bending radius is 5 mm or less, it can be made thin when folded. It can be said that the smaller the bending radius, the better, but the smaller the bending radius, the more likely it is to leave creases. The bending radius is preferably 0.1 mm or more, but may be 0.5 mm or more, or may be 1 mm or more. Even if the bending radius is 1 mm, it is possible to achieve a practically sufficient thinness when carried. The bending radius when folded is measured at the location of the symbol 11 in the schematic diagram of FIG. 1, and means the radius of the inside of the folded part when folded. The surface protective film described later may be located on the outside or inside of the folded folding display. Furthermore, the foldable display may be folded in three or four, or may be a rollable type, all of which are considered to fall within the scope of the foldable display of the present invention.

[0016] The polyester film for folding displays of the present invention may be used in any part of a folding display as long as it is a component of the folding display. Below, a typical configuration of a folding display and the part in which the polyester film of the present invention can be used are described using an organic EL display as an example. Hereinafter, the polyester film for folding displays of the present invention may be simply referred to as the polyester film of the present invention.

[0017] (Foldable OLED display) The essential component of a folding organic EL display is an organic EL module, and further includes a circular polarizing plate, a touch panel module, a front protective film, a back protective film, and the like, as required.

[0018] (Touch panel module) The mobile terminal device preferably has a touch panel. When an organic EL display is used, it is preferably arranged on the viewing side of the organic EL module, and further, it is preferable that the touch panel module is arranged between the organic EL module and the circular polarizing plate. The touch panel module preferably has a transparent conductive film having a transparent substrate such as a film and a transparent conductive layer arranged thereon. The polyester film in the present invention can be used as the transparent substrate of this transparent conductive film. When used as the transparent substrate of the transparent conductive film, it is preferable to provide the polyester film with a refractive index adjustment layer or a hard coat layer.

[0019] (Transparent conductive layer) In the present invention, the conductive layer preferably included in the touch panel module is not particularly limited as long as it is transparent and conductive, and examples of the conductive layer include a conductive filler-containing layer, a metal layer, a metal oxide layer, and a conductive polymer-containing layer.

[0020] In this case, the term "transparent" means that the conductive layer is transparent to the naked eye when processed to function as a touch panel, and the conductive portion itself does not necessarily have to be transparent. For example, even if an electrode pattern is provided so that the conductive layer functions as a touch panel, and the wiring itself is made of a metal such as gold and is opaque, the conductive layer can be considered transparent if the electrode pattern is not visible when the touch panel is viewed with the naked eye and an image can be observed.

[0021] As the conductive filler of the conductive filler-containing layer, fillers or fibers of metals such as gold, silver, copper, aluminum, nickel, titanium, iron, zinc, tin, or alloys thereof, metal oxide fillers, metal-coated synthetic fibers, conductive carbon fibers such as carbon nanotubes are preferred. As the metals, alloys, or metal oxide fillers, those having various shapes such as spherical particles, flat particles, flake-like particles, needle-like particles, and fibrous particles can be used. Among these, in terms of bending resistance, flake-like particles, needle-like particles, and fibrous fillers (fibers of metals or alloys thereof, fibers of metal oxides, metal-coated synthetic fibers, and conductive carbon fibers) are preferred, and fibrous fillers are even more preferred.

[0022] It is preferable that a binder resin is used in the conductive filler-containing layer. Examples of the binder resin include polyester resin, polyurethane resin, polyamide resin, and acrylic resin. Furthermore, it is preferable that these resins are crosslinked. The crosslinking agent may be used in accordance with each resin, and examples of the crosslinking agent include isocyanate compounds, epoxy resins, melamine compounds, oxazolines, carbodiimides, and compounds having two or more double bonds. The content of the conductive filler is preferably 10 to 400 parts by mass with respect to 100 parts by mass of the resin component constituting the conductive layer.

[0023] The conductive filler-containing layer can be provided by a coating method. The electrode pattern can be provided by processing the coating with chemical etching or laser etching, or by printing. Examples of the printing method include gravure printing, letterpress printing, offset printing, screen printing, and inkjet printing, and can be selected according to the characteristics of the paint and the fineness of the pattern.

[0024] Examples of metals for the metal layer include gold, silver, copper, aluminum, nickel, titanium, iron, zinc, tin, etc. The metal layer can be provided by a vapor deposition method, a sputtering method, etc., and the electrode pattern is preferably processed by chemical etching or laser etching after the metal layer is provided.

[0025] Examples of the metal oxide layer include ZnO, CeO2, Sb2O3, SnO2, indium tin oxide (abbreviation: ITO), In2O3, antimony-doped tin oxide (abbreviation: ATO), aluminum-doped zinc oxide (abbreviation: AZO), etc. The metal oxide layer can be provided by a sputtering method or the like, and the electrode pattern is preferably processed by chemical etching or laser etching after the metal oxide layer is provided.

[0026] As the conductive polymer-containing layer and the conductive polymer, for example, high molecular weight conductive agents such as aromatic conjugated poly(paraphenylene), heterocyclic conjugated polypyrrole, polythiophene, aliphatic conjugated polyacetylene, heteroatom-containing conjugated polyaniline, mixed conjugated poly(phenylenevinylene), multi-chain conjugated systems having multiple conjugated chains in the molecule, and conductive complexes which are polymers in which the above-mentioned conjugated polymer chains are grafted or block-copolymerized to a saturated polymer can be used.

[0027] The conductive layer containing a conductive polymer may contain the resin component listed in the conductive filler-containing layer. The content of the conductive polymer in the conductive layer containing a conductive polymer can be the same as that described in the conductive filler-containing layer. The conductive polymer-containing layer can be provided by a coating method, and the electrode pattern can be provided by the same method as that described for the conductive filler-containing layer.

[0028] When preparing the conductive layer, the conductive film may be heated to stabilize it (additives and layer reinforcement). In this case, the heat treatment temperature is preferably 30°C or higher, more preferably 50°C or higher, even more preferably 70°C or higher, particularly preferably 100°C or higher, and preferably 200°C or lower, more preferably 150°C or lower, and even more preferably 120°C or lower. If the heating temperature is higher than the lower limit, the stabilization of the conductive film is promoted, which is preferable. If the heating temperature is lower than the upper limit, the substrate that can be used is not limited to a substrate with high heat resistance, which is preferable. In this case, the substrate is required to have high flex resistance, i.e., no surface cracks, deformation, or breakage occurs when the substrate is bent even after heat treatment. The polyester film for touch panel module substrate of the present invention can maintain high flex resistance without losing or deteriorating the flex resistance after heat treatment.

[0029] The polyester film of the present invention is preferably used as a base film for a touch panel module.

[0030] As the base film for the touch panel module of the present invention, a polyester film having specific properties is used. The substrate film for the touch panel module of the present invention may be simply referred to as substrate film or polyester film.

[0031] The polyester film of the present invention may be a single-layer film made of one or more types of polyester resin, or when two or more types of polyester are used, it may be a multilayer film or an ultra-multilayer laminate film having a repeating structure.

[0032] Examples of polyester resins used in the polyester film include polyester films made of polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, or copolymers mainly made of these resin components. Among these, stretched polyethylene terephthalate films are particularly preferred in terms of mechanical properties, heat resistance, transparency, price, etc.

[0033] When a polyester copolymer is used for the polyester film, examples of the dicarboxylic acid component of the polyester include aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid; and polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. Examples of the glycol component include fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic glycols such as p-xylene glycol; and polyfunctional carboxylic acids such as 1,4-cyclohexanediol. and polyethylene glycol having an average molecular weight of 150 to 20,000. The mass ratio of the copolymerization components of the preferred copolymer is less than 20 mass %. When it is less than 20 mass %, the film strength, transparency, and heat resistance are preferably maintained.

[0034] In addition, in the production of polyester film, the intrinsic viscosity of at least one type of resin pellet is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance of the obtained film is improved, and disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the increase in filtration pressure of the molten fluid is not too large, and film production can be easily and stably operated, which is preferable.

[0035] The thickness of the polyester film is preferably 10 to 300 μm, more preferably 10 to 80 μm, and further preferably 25 to 75 μm. When the thickness is 10 μm or more, the effect of improving bending resistance, pencil hardness and impact resistance is observed, and when the thickness is 300 μm or less, it is advantageous for weight reduction and is excellent in flexibility, processability, handleability, etc.

[0036] The surface of the polyester film of the present invention may be smooth or uneven. However, since it is used for a touch panel of a display, deterioration of optical properties due to unevenness is not preferable. The haze is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is preferably 0.1% or more from the viewpoint of stable production, but it may be 0.3% or more.

[0037] As described above, in order to reduce haze, it is preferable that the unevenness of the film surface is not too large. However, in order to provide a certain degree of slipperiness from the viewpoint of handling, unevenness can be formed by blending particles into the surface polyester resin layer or by coating a coating layer containing particles during the film formation process.

[0038] The method of blending the particles in the polyester resin layer can be a known method. For example, it can be added at any stage of polyester production, but preferably it can be added as a slurry dispersed in ethylene glycol or the like at the stage of esterification, or after the completion of the transesterification reaction, and before the start of the polycondensation reaction, to proceed with the polycondensation reaction. It can also be performed by using a vented kneading extruder to blend the slurry of particles dispersed in ethylene glycol or water with the polyester raw material, or by using a kneading extruder to blend the dried particles with the polyester raw material.

[0039] Among them, a method is preferred in which aggregated inorganic particles are homogeneously dispersed in a monomer liquid that will become a part of the polyester raw material, and then the filtered product is added to the remainder of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, homogeneous dispersion of the particles and highly accurate filtration of the slurry can be easily performed, and when added to the remainder of the raw material, the dispersibility of the particles is good and new aggregates are unlikely to be generated. From this viewpoint, it is particularly preferred to add to the remainder of the raw material in a low temperature state before the esterification reaction.

[0040] In addition, the number of protrusions on the film surface can be further reduced by a method in which, after obtaining a polyester containing particles in advance, the pellets are mixed and extruded with pellets not containing particles (master batch method).

[0041] The polyester film may contain various additives, such as antistatic agents, UV absorbers, and stabilizers, within a range that maintains the total light transmittance in a preferred range.

[0042] The total light transmittance of the polyester film is preferably 85% or more, and more preferably 87% or more. With a transmittance of 85% or more, sufficient visibility can be ensured. The higher the total light transmittance of the polyester film, the better, but from the viewpoint of stable production, it is preferably 99% or less, and may be 97% or less.

[0043] The maximum heat shrinkage of the polyester film after heat treatment at 150°C for 30 minutes is preferably 0 to 2% or less, more preferably 0 to 1.5% or less, and even more preferably 0 to 1.0% or less. If the maximum heat shrinkage is 2% or less, flatness defects such as curling and waviness after attachment to a touch panel module or after hard coat application processing can be suppressed. If the maximum shrinkage is 0% or more, curling due to thermal dimensional change of the polyester film layer and the functional layer is unlikely to occur after various functional layers are added to the polyester film such as a hard coat in post-processing, and the yield when set on a touch panel is good, which is preferable.

[0044] The polyester film for folding displays of the present invention can provide sufficient pencil hardness to the hard coat film after laminating a hard coat layer. It is considered that in the conventional polyester film, after laminating a hard coat layer, the pencil hardness of the hard coat film is reduced due to deformation of the film in the thickness direction in the pencil hardness evaluation. In the present invention, by setting the indentation depth after removing the test force in the film thickness direction using a dynamic ultra-microhardness tester described below within a specific range, a high hardness can be achieved in the pencil hardness evaluation of the hard coat film. The indentation depth in the film thickness direction after the test force is removed is preferably 1.5 μm or less, more preferably 1.4 μm or less, and even more preferably 1.3 μm or less. If the indentation depth after the test force is removed (final deformation amount under load) is 1.5 μm or less, the film is less likely to deform in the thickness direction in the pencil hardness evaluation of the hard coat film after laminating the hard coat layer, and the pencil hardness can be increased. If the pencil hardness of the hard coat film can be increased, scratches and dents are less likely to occur on the display surface, and the visibility of the display is improved. It can be said that the lower the indentation depth after the test force is removed, the better, but in terms of stable production and saturation of the effect, it is preferably 0.3 μm or more, and more preferably 0.5 μm or more.

[0045] In order to reduce the indentation depth after the test force is removed, it is effective to adjust the refractive index in the thickness direction to 1.520 or less. As a means for adjusting the refractive index to 1.520 or less, as described later, examples of the means include setting conditions such as adjusting the stretch ratio in the bending direction or folding direction to a high value, setting the stretching temperature in the bending direction or folding direction to a low value, and setting the heat setting temperature to a high value, within a range in which other physical properties and the refractive index in the bending direction or folding direction can be controlled to a preferred range.

[0046] The polyester film for folding displays of the present invention does not cause creases, cracks, or breaks when folded, and can adjust the neutral plane of the display. The neutral plane refers to a surface where the inside is subjected to compressive stress and the outside is subjected to tensile stress when folded, but no stress is applied between them. In folding displays, a neutral plane is generally designed in the organic EL layer. The neutral plane can be adjusted by the elastic modulus and thickness of each layer. Therefore, the elastic modulus of the polyester film in the bending direction is preferably 2.7 GPa or less, more preferably 2.6 GPa or less, and even more preferably 2.5 GPa or less. It can be said that the bending property is improved by reducing the elastic modulus in the bending direction, but 1.8 GPa or more is preferable for adjusting the neutral plane. The elastic modulus in the folding direction is preferably 4.5 GPa or more, more preferably 4.6 GPa or more, and even more preferably 4.7 GPa or more. By increasing the elastic modulus in the folding direction, the flatness of the display surface can be maintained when the display is created. In addition, the touch panel module can be protected from external impact. The higher the elastic modulus in the folding direction, the more preferable it is, but from the viewpoint of film formability, it is preferably 8.0 GPa or less.

[0047] The surface of the polyester film of the present invention may be subjected to a treatment for improving adhesion to a resin forming a transparent conductive layer, an adhesive layer, a hard coat layer, or the like.

[0048] Examples of the surface treatment method include roughening treatment using sandblasting or solvent treatment, and oxidation treatment such as corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone or ultraviolet irradiation treatment, flame treatment, chromic acid treatment, or hot air treatment, and any of these methods can be used without any particular limitation.

[0049] In addition, the adhesion can be improved by an adhesion improving layer such as an easy-adhesion layer. The easy-adhesion layer can be made of any resin such as an acrylic resin, a polyester resin, a polyurethane resin, or a polyether resin, and can be formed by a general coating method, preferably a so-called in-line coating method.

[0050] The polyester film described above can be produced, for example, through a polymerization step in which inorganic particles are homogeneously dispersed in a monomer liquid that becomes a part of the polyester raw material, the dispersion is filtered, and then the dispersion is added to the remainder of the polyester raw material to polymerize the polyester, and a film formation step in which the polyester is melt-extruded through a filter into a sheet, which is cooled and stretched to form a base film.

[0051] Next, a method for producing a polyester film will be described in detail using an example in which polyethylene terephthalate (hereinafter, sometimes referred to as PET) pellets are used as the raw material for the base film, but the method is not limited thereto. In addition, the number of layers is not limited to a single layer or a multilayer structure.

[0052] After mixing and drying PET pellets in a predetermined ratio, the mixture is fed to a known melt lamination extruder, extruded from a slit die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder is sufficient, but in the case of producing a film with a multilayer structure, two or more extruders, two or more manifolds or merging blocks (e.g., merging blocks having a rectangular merging portion) are used to laminate multiple film layers constituting each outermost layer, and a sheet of two or more layers is extruded from a die and cooled on a casting roll to form an unstretched film.

[0053] In this case, it is preferable to perform high-precision filtration to remove foreign matter contained in the resin at any location where the molten resin is kept at about 280° C. during melt extrusion. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a filter material made of sintered stainless steel is preferable because it has excellent performance in removing aggregates and high-melting organic matter mainly composed of Si, Ti, Sb, Ge, and Cu.

[0054] Furthermore, the filtration particle size (initial filtration efficiency 95%) of the filter medium is preferably 20 μm or less, particularly preferably 15 μm or less. If the filtration particle size (initial filtration efficiency 95%) of the filter medium exceeds 20 μm, foreign matter with a size of 20 μm or more cannot be sufficiently removed. By using a filter medium with a filtration particle size (initial filtration efficiency 95%) of 20 μm or less to perform high-precision filtration of molten resin, productivity may decrease, but it is preferable to obtain a film with few protrusions due to coarse particles.

[0055] (Refractive index in bending direction) In the present invention, the refractive index of at least one of the longitudinal direction (machine flow direction) and the width direction of the polyester film is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. The refractive index of the bending direction of the polyester film is preferably 1.590 to 1.620, more preferably 1.591 to 1.600. Here, the bending direction refers to the direction perpendicular to the folding part (reference number 21) assumed in the use of a folding display, as shown by reference number 22 on the polyester film (reference number 2) in FIG. 2. When the refractive index of at least one of the longitudinal direction and the width direction is 1.590 to 1.620, there is little deformation when repeatedly folded, and there is no risk of deteriorating the image quality of the folding display, which is preferable. The refractive index is more preferably 1.591 to 1.600. Of course, the direction is preferably the bending direction. If the refractive index is 1.590 or more, there is no risk of cracks occurring in the folded portion direction after the bending test described below, and of course no breakage occurs, so that the visibility of the display can be maintained good. The refractive index of the polyester film can be effectively adjusted by adjusting the stretching ratio and stretching temperature. In addition, a relaxation process in the stretching direction and multi-stage stretching may be used to adjust the refractive index. When multi-stage stretching is performed, it is preferable to make the stretching ratios in the second and subsequent stages higher than the stretching ratio in the first stage.

[0056] By controlling the refractive index in at least one of the longitudinal direction (machine flow direction) and the width direction of the polyester film within the above range, and more preferably by controlling the refractive index in the bending direction within the above range, fatigue due to the compressive stress applied to the inside of the fold when folded can be reduced. It is believed that fatigue due to compressive stress occurs mainly in the crystalline portion, and fatigue is less likely to occur when there are fewer crystals in the bending direction. Therefore, it is believed that by lowering the refractive index, the amount of oriented crystals in the bending direction is reduced, and compression fatigue is suppressed.

[0057] Furthermore, the creep phenomenon caused by tensile stress applied to the outside of the fold when the material is folded can be suppressed by reducing the refractive index. Fatigue caused by tensile stress is thought to occur mainly in the amorphous portion, and the repeated application of stress causes molecular chains to align, resulting in deformation. It can be assumed that the fewer molecular chains aligned in the bending direction, the less deformation caused by alignment. Furthermore, since fatigue caused by tension can be suppressed with fewer amorphous portions, a higher degree of crystallinity, i.e., a higher density, is preferable.

[0058] In the present invention, the stretching ratio of the unstretched polyester sheet in at least one of the longitudinal direction (machine flow direction) and the transverse direction is preferably 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. The stretching direction is preferably the bending direction. A stretching ratio of 1.2 times or more is preferable since there is no deformation during post-processing such as hard coat coating, and a stretching ratio of 2.0 times or less is preferable since there is no unevenness in the thickness of the film. The stretching temperature is preferably 75 to 120°C, more preferably 75 to 105°C. The heating method during stretching may be a conventionally known method such as a hot air heating method, a roll heating method, or an infrared heating method. The above-mentioned means can be adopted. By setting the stretching temperature at 75 to 120° C., it is possible to prevent significant thickness unevenness due to stretching at the above-mentioned stretch ratio. In addition, by stretching at a temperature as low as possible within a range in which significant thickness unevenness does not occur as described above, it is possible to reduce the refractive index in the thickness direction.

[0059] (Refractive index in the direction of the fold) The refractive index of the polyester film in the direction perpendicular to the direction in which the refractive index is 1.590 to 1.620 is preferably 1.670 to 1.700. That is, the refractive index in the direction perpendicular to the bending direction (direction of the folded portion) is preferably 1.670 to 1.700. By making it 1.670 to 1.700, deformation when folded in the bending direction can be reduced. By making it 1.700 or less, cracks and breaks in the direction of the folded portion can be suppressed. By making it 1.670 or more, the flexibility in the bending direction can be improved and the surface hardness can be improved. 1.680 to 1.695 is more preferable. Methods for adjusting the refractive index in the direction perpendicular to the bending direction include the stretching ratio, stretching preheating temperature, stretching temperature, multi-stage stretching, and film relaxation. The stretching ratio is preferably 4.0 to 6.0 times, more preferably 4.4 to 6.0 times. In addition, the stretching preheating temperature in the direction perpendicular to the bending direction is preferably 70 to 110°C. When multi-stage stretching is performed in a direction perpendicular to the bending direction, it is preferable to set the stretching ratio higher in the second and subsequent stages than in the first stage. The film may be relaxed by 1 to 10% in either the machine flow direction (longitudinal direction) or the perpendicular direction (width direction).

[0060] (Refractive index in the thickness direction) The refractive index in the thickness direction is preferably 1.520 or less. By setting the refractive index to 1.520 or less, even if the refractive index in the bending direction is designed to be low, the decrease in hardness of the film surface can be suppressed, and both flexibility and surface hardness can be achieved. By setting the refractive index to 1.520 or less, the indentation depth after unloading the test force in the thickness direction is reduced, and the hardness of the film surface, particularly the pencil hardness of the hard coat film after lamination of the hard coat layer, can be improved. More preferably, it is 1.515 or less, even more preferably 1.510 or less, particularly preferably 1.505 or less, and most preferably 1.500 or less. The refractive index in the thickness direction is preferably low, but from the viewpoint of stable production, it is preferably 1.3 or more, and may even be 1.4 or more. It is particularly preferably 1.410 or more. It can be said that the above range can be achieved by increasing the stretch ratio in both the bending direction and the folding direction, but in order to control the refractive index in the thickness direction after controlling the refractive index in the bending direction and the width direction to a preferred range, it is preferable to set the conditions while checking the balance of the conditions of each process in the film formation process.

[0061] The method of controlling the refractive index in the thickness direction to the above range includes the preheating temperature, stretching temperature, and stretching ratio in the bending direction, the preheating temperature, stretching temperature, multi-stage stretching, high-ratio stretching, or heat fixing temperature setting in the folding direction. The preheating temperature in the bending direction is preferably 70°C to 110°C. The stretching temperature in the bending direction is preferably 75°C to 120°C. The stretching ratio in the bending direction is preferably 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. By lowering the stretching temperature and stretching at a low stretching ratio, the refractive index in the thickness direction can be effectively reduced while maintaining the flexibility in the bending direction. The preheating temperature in the folding direction is also preferably 75°C to 110°C. The stretching temperature is preferably 75°C to 120°C. The stretching ratio in the folding direction is preferably 4.0 to 6.0 times, more preferably 4.4 to 6.0 times. The refractive index in the thickness direction can be effectively reduced while maintaining or reducing the refractive index in the bending direction. Multi-stage stretching may be used as a method of high-ratio stretching. In this case, it is preferable to set the stretching ratio in the second stage higher than that in the first stage, since this allows for effective control of the refractive index. A method of stretching again after the crystallization step may also be used. Accelerated stretching, in which the stretching speed is increased from the initial stage to the latter stage of stretching, may also be used. The heat setting temperature is preferably 180 to 240° C. By carrying out heat setting, oriented crystallization in the stretching direction advances, and the refractive index in the thickness direction can be reduced. The reason why lowering the refractive index in the thickness direction improves the hardness of the film surface is not entirely clear, but it is thought that aromatic groups such as benzene rings in the molecular chain are oriented in the plane direction, which has the effect of suppressing deformation due to stress applied in the thickness direction.

[0062] (Regarding density of polyester film) The density of polyester film is 1.380g / cm 3 It is preferable that the density is 1.383 g / cm or more. 3 More preferably, it is 1.380 g / cm or more. 3By setting the density to 1.40 g / cm or more, it is possible to improve the flexibility and the film surface hardness, particularly the pencil hardness of the hard coat film after laminating the hard coat layer. The higher the density, the better. Although it depends somewhat on the presence or absence of particles in the film, it is preferable to set the density to 1.40 g / cm or more. 3 By setting the heat setting temperature during film formation to 180 to 240° C., crystallization can be promoted and the density can be effectively increased.

[0063] The bending direction of the polyester film is preferably set to correspond to the longitudinal direction (machine flow direction). This makes it easier to reduce the refractive index in the bending direction by biaxial stretching and improve the flexibility. That is, a polyester film is preferably obtained by stretching an unstretched polyester sheet in the longitudinal direction at a stretching ratio of 1.2 to 2.0 times, more preferably 1.7 to 2.0 times. In addition, it can be said that a preferred embodiment is to stretch the polyester sheet in the transverse direction at a stretching ratio of 4.0 to 6.0 times, more preferably 4.4 to 6.0 times.

[0064] In the present invention, the polyester film (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) Refractive index in the thickness direction is 1.520 or less (4) Density is 1.380 g / cm 3 End It is particularly preferable to have the above four characteristics simultaneously, but even if the combination is within the above-mentioned preferred manufacturing conditions, it may not necessarily be possible to obtain a film that satisfies all four characteristics simultaneously if the combination is not the best within each preferred manufacturing condition range, for example, a combination of a stretch ratio in the bending direction of 1.4 times or less, a stretch ratio in the folding direction of less than 4.4 times, and a heat setting temperature of 220° C. or less. In this case, the above four characteristics can be simultaneously satisfied by fine-tuning any of the conditions or a combination of them, such as increasing the stretch ratio in the bending direction to 1.7 times or more, increasing the stretch ratio in the folding direction to 4.4 times or more, increasing the heat setting temperature to about 230° C., or lowering the stretching temperature in the bending direction and / or the folding direction.

[0065] In order to adjust the film formability, film strength, thermal dimensional stability, and appearance defects, any film forming method such as stretching, relaxation, heat setting, and surface treatment may be used, but it can be said that a particularly preferred embodiment of the present invention is to control the refractive index and density of the film within the above-mentioned preferred ranges. By controlling the refractive index and density within the preferred ranges, it is possible to provide a polyester film suitable for a folding display, which has superior flex resistance and surface hardness compared to conventional films, particularly high pencil hardness of the hard coat film after laminating a hard coat layer.

[0066] Specifically, for example, PET pellets are thoroughly vacuum-dried, then fed to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to form an unstretched PET sheet. The unstretched sheet obtained is stretched 1.2 to 2.0 times, more preferably 1.7 to 2.0 times, in the longitudinal direction with a roll heated to 75 to 120°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is held by a clip and introduced into a hot air zone heated to 75 to 120°C, and after drying, is stretched 4.0 to 6.0 times, more preferably 4.4 to 6.0 times, in the transverse direction. Subsequently, the film can be introduced into a heat treatment zone at 180 to 240°C and heat-treated for 1 to 60 seconds. During this heat treatment process, a relaxation treatment of 0 to 10% may be performed in the transverse or longitudinal direction as necessary.

[0067] The intrinsic viscosity of the polyester film is preferably in the range of 0.50 to 1.0 dl / g. When the intrinsic viscosity is 0.50 dl / g or more, the impact resistance is improved and disconnection of the internal circuit of the display due to external impact is less likely to occur, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the increase in the filtration pressure of the molten fluid is not too large, which is preferable because film production is stable.

[0068] (Easy adhesion layer) In the present invention, in order to improve the adhesion between the polyester film and the transparent conductive layer or hard coat layer, it is also preferable to laminate an easy-adhesion layer on the polyester film. The easy-adhesion layer can be obtained by applying a coating liquid for forming the easy-adhesion layer to one or both sides of an unstretched or uniaxially stretched film in the longitudinal direction, heat-treating and drying as necessary, and then stretching the film in at least one direction that is not stretched. Heat treatment can also be performed after biaxial stretching. The final coating amount of the easy-adhesion layer is 0.005 to 0.20 g / m 2 It is preferable to control the coating amount to 0.005 g / m 2 On the other hand, if the coating amount is 0.20 g / m or more, adhesiveness is obtained, which is preferable. 2 If it is not more than this, blocking resistance can be obtained, which is preferable.

[0069] Resins contained in the coating liquid used for laminating the easy-adhesion layer can be, for example, polyester resins, polyether polyurethane resins, polyester polyurethane resins, polycarbonate polyurethane resins, acrylic resins, etc., and can be used without particular limitation. Examples of crosslinking agents contained in the coating liquid for forming the easy-adhesion layer include melamine compounds, isocyanate compounds, oxazoline compounds, epoxy compounds, carbodiimide compounds, etc. Two or more of each can also be mixed and used. Due to the nature of in-line coating, these are preferably applied using a water-based coating liquid, and the resins and crosslinking agents are preferably water-soluble or water-dispersible resins or compounds.

[0070] It is preferable to add particles to the easy-adhesion layer to give it easy slipperiness. The average particle size of the fine particles is preferably 2 μm or less. If the average particle size of the particles exceeds 2 μm, the particles are likely to fall off from the easy-adhesion layer. Examples of particles to be contained in the easy-adhesion layer include inorganic particles such as titanium oxide, barium sulfate, calcium carbonate, calcium sulfate, silica, alumina, talc, kaolin, clay, calcium phosphate, mica, hectorite, zirconia, tungsten oxide, lithium fluoride, and calcium fluoride, and organic polymer particles such as styrene-based, acrylic-based, melamine-based, benzoguanamine-based, and silicone-based particles. These may be added to the easy-adhesion layer alone, or two or more types may be added in combination.

[0071] The coating liquid can be applied by a known method, similar to the coating layer described above, such as reverse roll coating, gravure coating, kiss coating, roll brushing, spray coating, air knife coating, wire bar coating, and pipe doctor coating, which can be used alone or in combination.

[0072] (Hard coat layer) The polyester film preferably has a hard coat layer on at least one surface thereof in order to adjust the refractive index, improve the surface hardness, improve the bending resistance and cracking / cutting resistance, and block the adverse effect of oligomers precipitated from the polyester on the transparent conductive layer. The hard coat layer is preferably used by being positioned on the polyester film or on the easy-adhesion layer. The resin forming the hard coat layer may be any of acrylic, siloxane, inorganic hybrid, urethane acrylate, polyester acrylate, epoxy, and other resins without any particular limitation. Two or more types of materials may be mixed and used, or particles such as inorganic filler or organic filler may be added.

[0073] (Thickness of hard coat layer) The thickness of the hard coat layer is preferably 1 to 50 μm. If the thickness is 1 μm or more, it is preferable because it is cured sufficiently and has a high pencil hardness. Furthermore, if the thickness is 50 μm or less, curling due to cure shrinkage of the hard coat can be suppressed, and the handling properties of the film can be improved.

[0074] (Application method) The hard coat layer can be applied by any method including, but not limited to, a Mayer bar, a gravure coater, a die coater, a knife coater, etc., and can be appropriately selected depending on the viscosity and film thickness.

[0075] (Curing conditions) The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, and is preferably cured by ultraviolet rays or electron beams in order to reduce damage to the film.

[0076] (Pencil hardness) The pencil hardness of the hard coat layer is preferably 3H or more, more preferably 4H or more. With a pencil hardness of 3H or more, the surface is protected, and is not easily scratched or dented, and visibility is not reduced. In general, the pencil hardness of the hard coat layer is preferably high, but it may be 9H or less, 8H or less, or even 6H or less, and can be used without any practical problems.

[0077] (Characteristics of hard coat layer) The hard coat layer in the present invention can be used for the purpose of protecting a touch panel module or a display by increasing the pencil hardness of the surface as described above, and preferably has a high transmittance. The transmittance of the hard coat film is preferably 87% or more, more preferably 88% or more. If the transmittance is 87% or more, sufficient visibility can be obtained. The total light transmittance of the hard coat film is generally preferably as high as possible, but is preferably 99% or less from the viewpoint of stable production, and may be 97% or less. In addition, the haze of the hard coat film is generally preferably low, and is preferably 3% or less. The haze of the hard coat film is more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower the haze, the better, but is generally preferably 0.1% or more from the viewpoint of stable production, and may be 0.3% or more.

[0078] The hard coat layer may further have other functions added thereto. For example, a hard coat layer having the above-mentioned functions such as an antiglare layer having a certain pencil hardness, an antiglare antireflection layer, an antireflection layer, a low reflection layer, and an antistatic layer is preferably used in the present invention.

[0079] In order to make the electrode pattern of the transparent conductive layer less visible, it is also preferable that a refractive index adjustment layer is provided between the polyester film and the transparent electrode layer or between the hard coat layer and the transparent electrode layer. In that case, the hard coat layer itself may also serve as the refractive index adjustment layer, or a separate layer for refractive index adjustment may be laminated. Examples of the refractive index adjustment layer include a resin layer containing the above-mentioned refractive index adjustment particles, a fluorine-containing resin layer, an aromatic polyimide resin, an epoxy resin, a (meth)acrylic resin (acrylate, methacrylate compound), a polyester resin, a urethane resin, or other resin material having a high refractive index and containing an aromatic ring, a sulfur atom, or a bromine atom, and a layer of a precursor thereof, which can be provided by coating. In addition, inorganic layers such as ZnO, CeO2, Sb2O3, SnO2, indium tin oxide, In2O3, Al2O3, antimony-doped tin oxide, aluminum-doped zinc oxide, SiO2, and magnesium fluoride are also preferable as the refractive index adjustment layer, and these can be provided by a wet film formation method.

[0080] When a transparent conductive film is produced using the polyester film for touch panel modules of the present invention, preferred laminate structures include, for example, polyester film / transparent conductive layer, polyester film / easy adhesion layer / transparent conductive layer, polyester film / hard coat layer / transparent conductive layer, polyester film / easy adhesion layer / hard coat layer / transparent conductive layer, polyester film / refractive index adjustment layer (one layer or multiple layers with different refractive indexes) / transparent conductive layer, polyester film / easy adhesion layer / refractive index adjustment layer (one layer or multiple layers with different refractive indexes) / transparent conductive layer, polyester film / hard coat layer / refractive index adjustment layer (one layer or multiple layers with different refractive indexes) / transparent conductive layer, polyester film / easy adhesion layer / hard coat layer / refractive index adjustment layer (one layer or multiple layers with different refractive indexes) / transparent conductive layer, and the like. These laminate structure combinations may be present on one side of the polyester film, or may be present on both sides via the polyester film.

[0081] In the touch panel module of the folding display of the present invention, the polyester film of the present invention is used as a substrate constituting the touch panel module, but it is not necessary to use it for all of the films constituting the touch panel module. In the touch panel module of the folding display, in addition to the polyester film of the present invention, polyimide film, polyamide film, polyamideimide film, polyester film other than the polyester film of the present invention, polycarbonate film, acrylic film, triacetyl cellulose film, cycloolefin polymer film, polyphenylene sulfide film, polymethylpentene film, etc. can be used as a substrate film for the touch panel module according to suitability. EXAMPLES

[0082] Next, the present invention will be described with reference to examples and comparative examples. First, the evaluation methods of the characteristic values ​​carried out in the present invention will be described below.

[0083] (1) Intrinsic viscosity The film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution was centrifuged to remove inorganic particles, the flow time of the solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of the solvent alone were measured using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from the ratio of these times using the Huggins equation and assuming that the Huggins constant is 0.38.

[0084] (2) Bending resistance of polyester film sample (bending radius 1.5 mm) A polyester film sample with a size of 20 mm in the width direction × 110 mm in the flow direction is prepared. Using a no-load U-shaped stretch tester (Yuasa System Co., Ltd., DLDMLH-FS), the bending radius is set to 1.5 mm, and the sample is bent 200,000 times at a speed of 1 time / second. At that time, the sample is fixed at a position 10 mm from both ends of the long side, and the bending portion is 20 mm × 90 mm. Here, FIG. 1 is a schematic diagram for showing the bending radius when a folding display is folded, and considering the case where a polyester film is arranged on the inner surface of the folded state, a bending test is performed as a model with the portion indicated by the symbol 11 in FIG. 1 set to 1.5 mm. After the bending process, the sample was placed on a flat surface with the inner side of the bend facing down, and visual observation was performed. ○: No cracks or deformations were observed in the sample. ×: The sample has a crack or crease, and when placed horizontally, the maximum lift height is 5mm or more.

[0085] (3) Bending resistance of polyester film sample (bending radius 0.5 mm) In the same manner as in the bending test, the bending radius was set to 0.5 mm and the display was bent 200,000 times at a speed of 1 time / second. Here, FIG. 1 is a schematic diagram showing the bending radius when the foldable display is folded, and considering the case where a polyester film is arranged on the inner surface of the folded state, a bending test was performed as a model with the portion indicated by reference numeral 11 in FIG. 1 set to 0.5 mm. The film surface on the outer side of the bent portion was observed at 700 times magnification with a digital microscope (HIROX RH8800) to observe the presence or absence of wrinkles (cracks). In addition to the above-mentioned visual bending resistance test with a bending radius of 1.5 mm, this test was performed with the bending radius reduced to 0.5 mm, with the intention of evaluating the display in a state close to the actual use state of the foldable display in which a hard coat layer or other members are laminated or attached. In addition to the visual observation with a bending radius of 1.5 mm, this test is for detecting minute defects that are difficult to detect by visual inspection, such as defects that are prone to breakage or cracking. ○: No defects on the film surface on the outer side of the bend. ×: Broken or wrinkles (cracks) were observed on the film surface on the outer side of the bend.

[0086] (4) Bending resistance of polyester film sample after heat treatment (bending radius 1.5 mm) The sample film was cut to 210 mm x 300 mm in the horizontal direction, and the distance A between the marks was measured under a constant tension of 5 g. Next, the sample film was left in an oven with an atmosphere of 150 ° C. for 30 minutes without load, and then removed from the oven and cooled to room temperature. Then, the sample was cut to a size of 20 mm in the width direction x 110 mm in the length direction to prepare a polyester film sample. Using a no-load U-shaped stretch tester (Yuasa System Co., Ltd., DLDMLH-FS), the bending radius was set to 1.5 mm and the sample was bent 200,000 times at a speed of 1 time / second. At that time, the sample was fixed at a position 10 mm from both ends of the long side, and the bending area was 20 mm x 90 mm. Here, FIG. 1 is a schematic diagram showing the bending radius when the folding display is folded, and considering the case where a polyester film is arranged on the inner surface of the folded state, a bending test was performed as a model with the part indicated by the symbol 11 in FIG. 1 set to 1.5 mm. After the bending treatment, the sample was placed on a flat surface with the inside of the bend facing down, and visually observed. ○: No cracks or deformation (distortion) were observed in the sample. ×: The sample had a crack or crease, and when placed horizontally, the maximum floating height was 5 mm or more.

[0087] (5) Refractive index In accordance with JIS K 7142:2014 "Measurement method for refractive index of plastics (Method A)", the refractive index in the longitudinal direction, width direction, and thickness direction was determined using an Abbe refractometer (Atago Co., Ltd., NAR-4T, measurement wavelength 589 nm).

[0088] (6)Pencil hardness The pencil hardness of the hard coat film was measured using a sample at a load of 750 g and a speed of 1.0 mm / s in accordance with JIS K 5600-5-4: 1999. In the present invention, a value of 3H or more was considered to be acceptable.

[0089] (7) Total light transmittance, haze The haze was measured using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.).

[0090] (8) Density The density was measured according to the method compliant with JIS K 7112:1999 (density gradient tube method). (Unit: g / cm 3 ).

[0091] (9) Indentation depth after removing the test force The sample was cut into approximately 2 cm squares and fixed on a micro cover glass 18 × 18 mm (manufactured by Matsunami Glass Co., Ltd.) with an adhesive (Cemedine (registered trademark) High Super 30) on the surface opposite to the measurement surface. After adhesion and fixing, it was left at room temperature for 12 hours or more, and then the indentation depth (μm) after removing the test force was measured using a dynamic ultra-microhardness tester "DUH-211" (manufactured by Shimadzu Corporation) under the following conditions. <Measurement conditions> Test mode: Load-unload test Indenter used: 115 degree ridge angle, triangular pyramid indenter Indenter elastic modulus: 1.140×106N / mm 2 Indenter Poisson's ratio: 0.07 Test force: 50mN Load speed: 4.44mN / sec Load holding time: 2sec Unloading holding time: 0sec

[0092] (10) Maximum heat shrinkage rate The sample film was cut to 10 mm in the width direction and 250 mm in the length direction, and marks were made at 200 mm intervals along the long side in the direction to be measured, and the mark interval A was measured under a constant tension of 5 g. Next, the sample film was left in an oven at 150°C for 30 minutes without load, and then removed from the oven and cooled to room temperature. Then, the mark interval B was measured under a constant tension of 5 g, and the heat shrinkage rate (%) was calculated using the following formula. The heat shrinkage rate was measured at three equal positions in the width direction of the sample film, and the average value of the three points was taken as the heat shrinkage rate (%). Heat shrinkage rate (%) = [(AB) x 100] / A The sample film is cut so that the length and width of the sample differ in both the bending direction and the folding direction, and measurements are taken. The data in the direction where the measured value is greater is regarded as the maximum heat shrinkage rate (%).

[0093] (11) Elastic modulus (Young's modulus (unit: GPa)) The elastic modulus of the polyester film in the bending direction and the folding direction was measured at 23° C. in accordance with JIS K7127.

[0094] (Preparation of polyethylene terephthalate pellets (a)) A continuous esterification reactor consisting of a three-stage complete mixing tank having an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reactor, and the slurry was continuously fed to the first esterification reactor of the esterification reactor with TPA at 2 tons / hr, EG at 2 moles per mole of TPA, and antimony trioxide at an amount such that Sb atoms were 160 ppm relative to the produced PET, and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to the second esterification reactor, and EG distilled from the first esterification reactor was fed to the second esterification reactor at 8% by mass relative to the produced polymer (produced PET), and further, an EG solution containing magnesium acetate in an amount such that Mg atoms were 65 ppm relative to the produced PET and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260°C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that the P atom was 20 ppm relative to the produced PET was added, and the reaction was carried out at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reactor was continuously fed to a three-stage continuous polycondensation reactor to carry out polycondensation, and further filtered with a stainless steel sintered filter medium (nominal filtration accuracy of 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.62 dl / g.

[0095] (Preparation of polyethylene terephthalate pellets (b)) In the same manner as in the production process of polyethylene terephthalate pellets (a), except for adjusting the residence time of the third esterification reaction, the intrinsic viscosity was adjusted to 0.580 dl / g to obtain polyethylene terephthalate pellets (b).

[0096] (Preparation of polyethylene terephthalate pellets (c)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (c) having an intrinsic viscosity of 0.75 dl / g.

[0097] (Polymerization of urethane resin) A four-neck flask equipped with a stirrer, a Dimroth condenser, a nitrogen inlet tube, a silica gel drying tube, and a thermometer was charged with 72.96 parts by mass of 1,3-bis(isocyanate methyl)cyclohexane, 12.60 parts by mass of dimethylolpropionic acid, 11.74 parts by mass of neopentyl glycol, 112.70 parts by mass of polycarbonate diol having a number average molecular weight of 2000, and 85.00 parts by mass of acetonitrile and 5.00 parts by mass of N-methylpyrrolidone as a solvent, and stirred at 75°C for 3 hours under a nitrogen atmosphere, and it was confirmed that the reaction liquid reached a predetermined amine equivalent. Next, the reaction liquid was cooled to 40°C, and then 9.03 parts by mass of triethylamine was added to obtain a polyurethane prepolymer D solution. Next, 450g of water was added to a reaction vessel equipped with a homodisper capable of high-speed stirring, and the temperature was adjusted to 25°C. While stirring and mixing at 2000 min-1, an isocyanate group-terminated prepolymer was added and dispersed in water. Thereafter, acetonitrile and a portion of the water were removed under reduced pressure to prepare a water-soluble polyurethane resin (A) having a solid content of 35 mass %.

[0098] (Polymerization of Water-soluble Carbodiimide Compounds) In a flask equipped with a thermometer, a nitrogen gas inlet tube, a reflux condenser, a dropping funnel, and a stirrer, 200 parts by mass of isophorone diisocyanate and 4 parts by mass of 3-methyl-1-phenyl-2-phospholene-1-oxide as a carbodiimide catalyst were added, and the mixture was stirred for 10 hours at 180°C under a nitrogen atmosphere to obtain isocyanate-terminated isophorone carbodiimide (polymerization degree = 5). Next, 111.2 g of the obtained carbodiimide and 80 g of polyethylene glycol monomethyl ether (molecular weight 400) were reacted at 100°C for 24 hours. Water was gradually added to the mixture at 50°C to obtain a yellow, transparent, water-soluble carbodiimide compound (B) with a solid content of 40% by mass.

[0099] (Preparation of Coating Solution for Forming Adhesion Layer) The following coating materials were mixed to prepare a coating solution. Water 16.97 parts by mass Isopropanol 21.96 parts by weight Polyurethane resin (A) 3.27 parts by weight Water-soluble carbodiimide compound (B) 1.22 parts by mass Particles 0.51 parts by mass (Silica sol with average particle size of 40 nm, solid content concentration of 40% by mass) Surfactant 0.05 parts by weight (Silicone-based, solids concentration 100% by mass)

[0100] (Preparation of hard coat coating solution a) 0.1 parts by mass of a leveling agent (BYK307, manufactured by BYK Japan, concentration 100%) was added to 100 parts by mass of a hard coat material (Opstar (registered trademark) Z7503, manufactured by JSR Corporation, concentration 75%), and the mixture was diluted with methyl ethyl ketone to prepare a hard coat coating solution a with a solid content concentration of 40% by mass.

[0101] (Preparation of hard coat coating solution b) 95 parts by mass of pentaerythritol triacrylate (A-TMM-3, manufactured by Shin-Nakamura Chemical Co., Ltd., solid content concentration 100%), 5 parts by mass of a photopolymerization initiator (Irgacure (registered trademark) 907, manufactured by BASF Japan, solid content concentration 100%), and 0.1 parts by mass of a leveling agent (BYK307, manufactured by BYK Japan, solid content concentration 100%) were mixed and diluted with a solvent of toluene / MEK=1 / 1 to prepare a hard coat coating solution b with a concentration of 40% by mass.

[0102] (Preparation of coating solution containing conductive fibrous filler and metal nanowires) A mixed solution of 0.6 g of silver nitrate (manufactured by Wako Pure Chemical Industries, Ltd.), 36 g of 1.4 wt% polyvinylpyrrolidone (PVP, manufactured by Wako Pure Chemical Industries, Ltd., average molecular weight 360,000) in ethylene glycol (EG, manufactured by Kishida Chemical Co., Ltd.), 4 g of 165 ppm iron chloride (III) (manufactured by Kishida Chemical Co., Ltd.) in EG solution, and 109 g of EG was prepared and used as reaction solution 1. Reaction solution 1 was heated from room temperature to 130°C using a personal synthesis device (ChemiStation, PPV-CTRL1, manufactured by Tokyo Rikakikai Co., Ltd.) and reacted for 187 minutes. A cylindrical filter paper (No. 86R, retention particle size 1 μm, 20 mm × 90 mm, manufactured by Advantec Toyo Co., Ltd.) filled with 20 mL of reaction solution 1 was placed in a 300 mL beaker, and isopropyl alcohol (manufactured by Junsei Chemical Co., Ltd.) was poured on the outside of the cylindrical filter paper so that it was at the same height as the reaction solution inside the cylindrical filter paper. After one week, the solution inside the cylindrical filter paper was collected and used as a metal nanowire-containing coating solution.

[0103] Example 1 Pellets of polyethylene terephthalate (a) were fed to an extruder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded from a die in the form of a sheet, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. The unstretched film was uniformly heated to 75°C using a heating roll, heated to 85°C using a non-contact heater, and roll-stretched (longitudinal stretching) 1.4 times. The above-mentioned coating solution for forming an easy-adhesion layer was applied to both sides of the obtained uniaxially stretched film by a roll coating method, and then dried at 80°C for 20 seconds. The coating amount after the final (biaxial stretching) drying was 0.06g / m 2 The film was then introduced into a tenter, preheated at 105°C, transversely stretched 4.0 times at 95°C, fixed in width, heat-set at 230°C for 5 seconds, and further relaxed in the width direction by 4% at 180°C to obtain a polyethylene terephthalate film with a thickness of 50 μm.

[0104] (Examples 2 to 3) A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to that shown in Table 1.

[0105] Example 4 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the width direction was changed to 4.4 times and the heat setting temperature was changed to 220°C.

[0106] (Examples 5 and 6) A polyester film was obtained in the same manner as in Example 4, except that the stretching ratio in the longitudinal direction was changed as shown in Table 1.

[0107] Example 7 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the width direction was changed to 5.5 times and the heat setting temperature was changed to 190°C.

[0108] (Examples 8 to 9) A polyester film was obtained in the same manner as in Example 7, except that the stretching ratio in the longitudinal direction was changed as shown in Table 1.

[0109] Example 10 A polyester film was obtained in the same manner as in Example 5, except that in the production process of Example 5, after the film was stretched in the longitudinal direction, a 10% relaxation heat treatment was carried out at 100°C.

[0110] Example 11 In the manufacturing process of Example 5, the clips were released at 200°C after heat setting, and a relaxation heat treatment was performed in the longitudinal and width directions, but the same procedure was followed to obtain a polyester film. The tenter speed and the take-up roll speed were adjusted so that the relaxation rate in the longitudinal direction was 3%. The relaxation in the width direction was left in a free state.

[0111] Example 12 A polyester film was obtained in the same manner as in Example 1, except that the temperature during longitudinal stretching was changed to 75°C and the heat setting temperature was changed to 220°C.

[0112] Example 13 A polyester film was obtained in the same manner as in Example 1, except that the temperature during longitudinal stretching was changed to 75°C, the stretching ratio was changed to 1.2 times, and then the stretching ratio was changed to 5.0 times in the width direction.

[0113] Example 14 A polyester film was obtained in the same manner as in Example 3, except that the longitudinal stretching in Example 3 was a two-stage stretching in which the first stage stretching ratio was 1.2 times and the second stage stretching ratio was 1.67 times. The total longitudinal stretching ratio was about 2.0 times.

[0114] Example 15 A polyester film was obtained in the same manner as in Example 5, except that the preheating temperature during widthwise stretching was changed to 95°C and the heat setting temperature was changed to 190°C.

[0115] Example 16 A polyester film was obtained in the same manner as in Example 2, except that the stretching in the width direction in Example 2 was changed to two-stage stretching, the stretching ratio in the first stage was 1.5 times, the stretching ratio in the second stage was 4.0 times, and the heat setting temperature was changed to 190° C. The total stretching ratio in the width direction was 6.0 times.

[0116] (Examples 17 to 18) A polyester film was obtained in the same manner as in Example 2, except that the thickness was changed as shown in Table 1.

[0117] (Example 19) A polyester film was obtained in the same manner as in Example 1, except that the relaxation heat treatment in the width direction was not carried out in the production process of Example 1.

[0118] (Example 20) An unstretched film was prepared in the same manner as in Example 1, and the unstretched film was preheated at 75°C in a tenter and stretched laterally to 1.4 times at 85°C. The above-mentioned coating liquid for forming an easy-adhesion layer was applied to both sides of the obtained uniaxially stretched film by roll coating, and then dried at 80°C for 20 seconds. The final coating amount after drying (after biaxial stretching) was 0.06 g / m 2The film was uniformly heated to 105°C using a heating roll, heated to 95°C using a non-contact heater, and roll-stretched (longitudinal stretching) at 4.0 times its original size. The film was then fixed in width and heat-set at 230°C for 5 seconds to obtain a polyethylene terephthalate film with a thickness of 50 μm.

[0119] Example 21 A polyethylene terephthalate film having a thickness of 50 μm was obtained in the same manner as in Example 1, and then the hard coat coating solution b was applied thereto to obtain a hard coat film.

[0120] Comparative Example 1 A polyester film was obtained in the same manner as in Example 1, except that the film was not stretched in the longitudinal direction but was stretched only in the width direction, that is, uniaxially stretched in the transverse direction.

[0121] Comparative Example 2 A polyester film was obtained in the same manner as in Example 7, except that the film was not stretched in the longitudinal direction but was stretched only in the width direction, that is, uniaxially stretched in the transverse direction.

[0122] (Comparative Examples 3 to 7) A polyester film was obtained in the same manner as in Example 1, except that the heat setting temperature was changed to 220° C., and the PET pellets and thickness were as shown in Table 1. As described above, in Comparative Examples 3 to 7, the heat setting temperature was lower than that in Example 1, and the combination of the longitudinal and transverse stretching ratios was not the best within the preferable range of conditions. As shown in Table 1, the refractive index in the thickness direction increased, the indentation depth after the test force was removed was large, and the pencil hardness after the hard coat layer was laminated was smaller than that in each Example.

[0123] Comparative Example 8 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to 2.7 times and the heat setting temperature was changed to 220°C.

[0124] Comparative Example 9 A polyester film was obtained in the same manner as in Example 1, except that the stretching ratio in the longitudinal direction was changed to 3.4 times.

[0125] Comparative Example 10 A polyester film was obtained in the same manner as in Example 4, except that the heat setting temperature was changed to 100°C.

[0126] Comparative Example 11 A polyester film was obtained in the same manner as in Example 13, except that the longitudinal stretching temperature was changed to 130°C.

[0127] Comparative Example 12 A polyester film was obtained in the same manner as in Example 1, except that the preheating temperature in the width direction was changed to 120°C.

[0128] Using a Mayer bar, hard coat coating solution a was applied to one side of the film prepared above so that the film thickness after drying would be 5 μm, and the film was dried at 80° C. for 1 minute, and then irradiated with ultraviolet light (accumulated light amount 200 mJ / cm 2 ) to obtain a hard coat film. Thereafter, a metal nanowire-containing coating solution was applied to the surface of the prepared hard coat layer using a Mayer bar so that the film thickness after drying would be 5 μm, and the coating was dried at 80° C. for 10 minutes to obtain a transparent conductive polyester film. The evaluation results are shown in Table 1.

[0129] The transparent conductive polyester film prepared above was incorporated into a touch panel module to create a smartphone-type folding display that can be folded in half at the center of the entire display, which has a radius of 3 mm corresponding to the bending radius in FIG. 1. The touch panel module including the transparent conductive polyester film made of the polyester film of each example was satisfactory in operation and visibility as a smartphone that can be folded in half at the center and carried around. In addition, the surface was not dented by external force. Here, since the maximum heat shrinkage rate of the polyester film was somewhat large in Examples 6 to 9, 15, and 16, the results were somewhat inferior to the other examples in terms of the small amount of curling after heat processing, but were satisfactory overall. On the other hand, the folding displays using the polyester film or hard coat film of each comparative example seemed to cause image distortion at the folding part of the display as the frequency of use increased, which was not very preferable. In addition, some of the displays had dents and scratches on the surface.

[0130] [Table 1]

[0131] [Table 2] [Industrial Applicability]

[0132] A foldable display using the polyester film for touch panel module substrate of the foldable display of the present invention maintains mass productivity, and the polyester film located in the touch panel module of the foldable display does not deform after repeated folding, so that no image distortion occurs at the folded portion of the display. In particular, a mobile terminal device or image display device equipped with a foldable display using the polyester film of the present invention as a touch panel module substrate provides beautiful images, is highly functional, and has excellent convenience such as portability. [Explanation of symbols]

[0133] 1: Foldable display 11: Bending radius 2: Polyester film for touch panel module of foldable display 21: Folding section 22: Bending direction (direction perpendicular to the folding part)

Claims

1. A polyester film for use as a substrate for touch panel modules in foldable displays that satisfies the following conditions: (1) The refractive index in the bending direction is 1.590 to 1.620 (2) The refractive index in the direction of the fold is 1.670 to 1.700 (3) A refractive index in the thickness direction is 1.520 or less. (4) Density is 1.380 g / cm 3 End (5) The polyester film is a biaxially oriented polyethylene terephthalate film. (6) No cracks or deformations were observed in the bending resistance evaluation (bending radius 1.5 mm) after heat treatment at 150°C for 30 minutes. (Here, the bending direction refers to the direction perpendicular to the fold when folding the polyester film.)

2. 2. The polyester film for use as a substrate for a touch panel module of a folding display according to claim 1, having an elastic modulus of 2.7 GPa or less in a bending direction and an elastic modulus of 4.5 GPa or more in a direction of the folding portion.

3. 3. The polyester film for use as a substrate for a touch panel module of a folding display according to claim 1 or 2, which has a total light transmittance of 85% or more, a haze of 3% or less, and a maximum heat shrinkage rate of 2% or less.

4. The bending resistance evaluation (bending radius 1.5 mm) is performed by evaluating whether or not cracks or deformation occurs when the polyester film for touch panel module substrate of a foldable display according to any one of claims 1 to 3 is placed on a flat surface with the inside of the bend facing down after a no-load U-shaped stretching test in which the polyester film is heat-treated at 150°C for 30 minutes and then bent 200,000 times at a bending radius of 1.5 mm and a speed of 1 time / second.

5. The polyester film for a touch panel module substrate of a folding display according to any one of claims 1 to 4, wherein the polyester film for a touch panel module substrate of a folding display has an easy-adhesion layer on at least one side thereof.

6. The polyester film for a touch panel module substrate of a folding display according to any one of claims 1 to 5, wherein the polyester film for a touch panel module substrate of a folding display has a hard coat layer having a thickness of 1 to 50 μm on at least one side of the polyester film for a touch panel module substrate of a folding display.

Citation Information

Patent Citations

  • Film

    JP1998316783A

  • Polyethylene terephthalate resin film and its manufacturing method

    JP2009149066A

  • Method of processing hard coat film, hard coat film and protective film

    JP2010228391A

  • Biaxially oriented polyester film

    JP2012107080A

  • Manufacturing method for foldable hard coating film

    JP2016155124A